Urbanizing food systems: exploring the interactions of food access dimensions for sustainability - Anandhi, Aavudai; Usher, Kareem M.; Schulterbrandt Gragg, Richard; Jiru, Mintesinot (Frontiers in Sustainable Food Systems, 2025)
This paper aims to conceptualize the dimensions of food access to enhance urban food system sustainability by analyzing the cause-effect interactions between the five dimensions and the urban food environment and using spider web diagrams to illustrate their interrelationships in terms of community perception and objectivity. Various studies have conceptualized access as a construct of five dimensions. This new expanded view supports both objective and perceived aspects of access and values the knowledge of residents through community-based participatory research, thereby providing a more complete understanding of access. This study, building on Usher’s broader themes of spatiality, objectivity and perception, analyzes the cause-effect interactions between the five dimensions and the urbanizing food environment by expanding and modeling the dimensions of access and their interactions critical to the analysis and decision-making processes of sustainable urbanizing food systems. With the use of spider web diagrams, we demonstrate the degree of interactions among the five dimensions (availability, accessibility, acceptability, accommodation, availability, and affordability), with respect to the community perception and objectivity. We used the DPSIR causal framework to analyze the cause-effect relations between the five dimensions and the DPSIR components: drivers, pressures, state, impact, and response. The five dimensions are further conceptualized for spiderweb and DPSIR for low, medium and high interactivity. The conceptualizations are applied to three case studies from the literature. This paper, additionally, integrates insights from Systems Thinking, which has been pivotal in understanding the complex, interconnected nature of sustainable food systems. Furthermore, ecosystem approaches to health, which emphasize systemic and holistic perspectives, are also considered. These approaches highlight the interdependence between ecological and human health, advocating for integrated strategies that promote both environmental and human well-being.